Management of anxiety disorders in children who survived the novel coronavirus infection - G.R. Sagitova; V.A. Shuldais; N.V. Klyueva; E.M. Shaforostova; I.B. Konotopova (LCC «Medicine-Inform», 2022)
G.R. Sagitova1, V.A. Shuldais2, N.V. Klyueva2, E.M. Shaforostova1, I.B. Konotopova2 1Astrakhan State Medical University, Astrakhan, Russian Federation 2Children's City Polyclinic No.4, Astrakhan, Russian Federation Background: currently, the term "post-COVID conditions" has been commonly used in healthcare practices. It includes impairments of multiple human organ systems. Many international and Russian researchers have mentioned in their studies that such patients, including children, are at a higher risk of developing psychoneurological disorders. Aim: to assess the clinical efficacy of a syrup, containing choline, glycine, lysine, B vitamins, zinc, magnesium, lemon balm and mint extracts to cope with the manifestations of anxiety disorders developed in children after COVID-19 infection. Patients and Methods: this prospective study involved 65 children, 7-11 years old, who had mild cases of COVID-19 and developed manifestations of anxiety disorders. All patients were given recommendations including nutritional therapy, sleep and rest routine, walking into the fresh air, and limiting the time children spend on their phones, computers and TV. 40 patients, 20 of whom were girls, of the treatment group (TG) additionally received a biologically active supplement (BAS), "Kidz Syrup with lemon balm and mint", at the dosage of 1 stick (5 ml) 3 times a day for 42 days. 25 children, 16 of whom were girls, were included in the control group (CG), receiving only routine treatment. The duration of follow-up period was 42 days. A questionnaire was filled out by children's parents to assess the severity of asthenic syndrome. Results: after one month of treatment with the BAS added to the routine therapy, the TG patients demonstrated trends in lower severity of all symptoms of asthenic syndrome vs that at the baseline (р<0.05, unpaired t-test). Such trends were not reported in the control group (р>0.05, unpaired t-test). Parents of the TG children reported more physical activity and interest, better sleep and appetite, normalizing kids' behavior and improving relationships. In the CG patients, receiving routine therapy, these changes were less pronounced. Seven of 40 patients did not like taking the syrup because of the unpleasant syrup taste. It was the reason why three of 40 patients declined further participation in the study. None of the children reported allergic reactions. Conclusion: a biologically active substance "Kidz syrup with lemon balm and mint" given to the primary school-aged children who survived COVID-19 and developed manifestations of anxiety disorders, helps to improve their ability to manage emotional distress, concentrate attention and memory, and has the protective effect against the increasing mental burdens. Keywords: children, COVID-19, post-COVID conditions, anxiety disorders, biologically active supplement, lemon balm and mint. For citation: Sagitova G.R., Shuldais V.A., Klyueva N.V. et al. Management of anxiety disorders in children who survived the novel coronavirus infection. Russian Journal of Woman and Child Health. 2022;5(4):340-345 (in Russ.). DOI: 10.32364/2618-8430-2022-5-4-340-345.